2016
DOI: 10.1007/s00261-016-0887-4
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and clinical findings in segmental arterial mediolysis (SAM)

Abstract: Segmental arterial mediolysis (SAM) is an uncommon, non-atherosclerotic, non-inflammatory arteriopathy that tends to affect the medium-sized splanchnic branches of the aorta along with renal, carotid, cerebral, and coronary arteries. The clinical presentation ranges from asymptomatic to severe, life-threatening intra-abdominal hemorrhage and shock. SAM overlaps clinically and radiologically with other inflammatory vasculitides. This article describes the pathologic-radiologic correlation, imaging findings, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(66 citation statements)
references
References 19 publications
0
63
0
3
Order By: Relevance
“…To the best of our knowledge, only four cases of SAM involving the intrahepatic arteries have been previously reported [3,5,7,9]. As the occurrence of SAM in the intrahepatic artery is extremely rare, physicians would likely not consider SAM when assessing patients with hepatic artery aneurysm.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…To the best of our knowledge, only four cases of SAM involving the intrahepatic arteries have been previously reported [3,5,7,9]. As the occurrence of SAM in the intrahepatic artery is extremely rare, physicians would likely not consider SAM when assessing patients with hepatic artery aneurysm.…”
Section: Discussionmentioning
confidence: 98%
“…For example, the first reported patient with SAM died because of hemorrhagic shock [7]. Of the three remaining patients, two underwent coil embolization for bleeding from the aneurysm and painful symptoms, or rupture of the aneurysm with fistulous connection to the portal vein [3,9]. In contrast, Tomonaga et al reported a patient with ruptured SAM who successfully underwent conservative treatment [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations